Influence of diamond surface chemical states on the adhesion strength between Y2O3 film and diamond substrate. (5th September 2016) - Hua, Chenyi; Guo, Jianchao; Liu, Jinlong; Yan, Xiongbo; Zhao, Yun; Chen, Liangxian; Wei, Junjun; Hei, Lifu; Li, Chengming
Abstract: The Y2 O3 film deposited on chemical oxidation diamond substrate exhibited high adhesion strength and survived thermal shock at 800 °C. Oxygenated functionalization of the diamond surface had been successfully achieved via wet chemical oxidation with the increase in O/C atomic ratio from 0.04 to 0.13. The surface energy of the diamond substrate was significantly improved from 35.7 mJ/m 2 to 61.4 mJ/m 2 . After depositing Y2 O3 film on the diamond substrate, the COY bonds were observed at the interface. In addition, the quantity of COY bonds significantly increased with the chemisorbed oxygen concentration increasing. The critical scratch load of Y2 O3 film deposited on chemical oxidation diamond substrate increased from 22.5 N to 34.1 N. Furthermore, the Y2 O3 film deposited on chemical oxidation diamond substrate can withstand harsh thermal change and protect the diamond substrate from elevated temperature oxidation in atmospheric air without showing degradation of infrared optical performance. Graphical abstract: Highlights: Diamond surface modification was achieved via wet chemical oxidation. The surface energy of diamond substrates improved from 35.7 mJ/m 2 to 61.4 mJ/m 2 . The critical load of Y2 O3 film deposited on diamond substrate increased from 22.5 N to 34.1 N. The sample showed no infrared optical performance degradation after thermal shock test.